Konstruksi Pemberitaan Anggaran Janggal Rancangan APBD DKI Jakarta 2020 Pada Program MetroTVNewsRoom dan Mata Najwa TRANS7 (Analisis Framing Robert Entman) - Anastasia Reski Dua Lembang; Christanto Puji R; Muhammad Zamroni (ROLLING, 2022)
The present study discusses the reporting construction of two talk show programs, MetroTVNewsRoom and Mata Najwa The present study aims to find out the reporting construction of MetroTVNewsRoom and Mata Najwa TRANS7 in reporting. Unusual 2020 regional budget plan of DKI Jakarta case These media possess different backgrounds. Employing descriptive qualitative study, this study spells out in detail the problem of the study. The data were analyzed using Robert N. Entman’s framing model analysis. The present study employed the theory of reality construction, ideology, and media ownership. The result of the analysis put evidence that Metro TV, through “MetroTVNewsRoom” in the episode of “Heboh anggaran “aneh” Pemprov DKI and Trans7, through “Mata Najwa” in the episode of “Buka-bukaan Anggaran), are different in constructing the reality and framing the case. As a media whose owner has declared support for Governor Anies Baswedan, MetroTvNesroom is affected by its frame; besides, the media owner plays pivotal role in constructing news reality. Meanwhile, Mata Najwa, as a program whose owner does not have a political interest in Governor Anies Baswedan’s governance, is sharper in delivering facts and criticism than MetroTVNewsRoom is.